Students’ Social Interaction in Multi-Ethnic Schools - Tri Astuti; Masrukhi Masrukhi; Ngabiyanto Ngabiyanto (International Conference on Science, Education, and Technology, 2023)
In Tegal city, there is a multi-ethnic school. Its students have different cultural and ethnic backgrounds. This school should manage these differences properly so that there is no conflict. The research objectives are (1) to examine and analyze social interactions among students in multi-ethnic schools and (2) to analyze the obstacles students face in conducting social interactions in multi-ethnic schools. The research location is Tunas Hidup Harapan Kita Elementary School, a multi-ethnic school in Tegal. Its method was qualitative with a case study type. The research method used is qualitative with a case study type. Data collection techniques include observation, interviews, and observations. The data validity testing uses the method and source triangulation technique. Data analysis uses compiling data systematically, organizing data into categories, describing data, choosing valid data, and making conclusions. The study result shows that students' social interactions occur in cooperation, competition, and competition. The obstacles faced in social interaction at school are characteristics of immature students, habituation in the family environment, and the density of student activities. This article concludes that the social environment influences students' social interaction in multi-ethnic schools. Social interaction goes well based on the value of tolerance. To minimize conflict between students, the school develops its value.